Pengaruh Model Project Based Learning Terhadap Kemampuan Menulis Karangan Narasi Siswa Kelas X SMKIT MA Bolang - Utami, Shinta Aulia (Jurnal Artikula, 2024)
This research aims to determine the influence of the Project Based Learning Model on students of X SMKIT MA Bolang. This research was conducted using the experimental method. Class X students for the 2024/2025 academic year were used as the population. The samples taken were class X AP1 and class X AP3 with a total of 92 students. The sample technique uses Random Sampling. The results of posttest calculations using the Project Based Learning learning model obtained Mean (x ̃) = 81.06, Median (Me) = 81.00, Mode (Mo) = 80.00, Variance = 21,596, and Standard Deviation = 4,647. Meanwhile, posttest calculations using the conventional data processing learning model obtained Mean (x ̃)= 73.47, Median (Me) = 74.50, Mode (Mo) = 75, Variance = 15,568, and Standard Deviation = 3,946. Based on the data above, it can be said that the Project Based Learning learning model is considered good, while the Conventional learning model is considered sufficient. From the results of the analysis above, it can be concluded that there is a positive influence of using the Project Based Learning learning model on the ability to write narrative essays of class X SMKIT MA Bolang students. Keywords: Project Based Learning Model, Writing Skills, Narrative Essay